Paradoxical para-hisian pacing response - Efe, Tolga Han; Merovci, Idriz; Çalapkuyu, Muhammed Yunus; Özdemir Al, Ceren; Kara, Meryem; Koçyiğit Burunkaya, Duygu; Özcan Çetin, Elif Hande; Korkmaz, Ahmet; Özeke, Özcan; Çay, Serkan; Özcan, Fırat; Aras, Dursun; et al. (MediaSphere Medical LLC, 2023)
Para-Hisian pacing (PHP) is among the most useful maneuvers in cardiac electrophysiology during sinus rhythm and identifies whether retrograde conduction is dependent on the atrioventricular (AV) node. In this maneuver, the retrograde activation time and pattern are compared during capture and loss of capture of the His bundle while pacing from a paraHisian position. A common misconception about PHP is that it is useful only for septal accessory pathways (APs). However, even with left or right lateral pathways, as long as pacing from the para-Hisian region conducts to the atrium with the activation sequence being analyzed, it can be used to determine whether that activation is AV node–dependent or AP-dependent.
Keywords: Atrioventricular Re-Entrant Tachycardia; Elecrophysiological Maneuvers; Para-Hisian Pacing